Michael Acceptors as Cysteine Protease Inhibitors - Santos, Maria M.M.; Moreira, Rui (Mini Reviews in Medicinal Chemistry, 2007)
Cysteine proteases selectively catalyze the hydrolysis of peptide bonds. Uncontrolled, unregulated, or undesired proteolysis can lead to many disease states including emphysema, stroke, viral infections, cancer, Alzheimer's disease, inflammation, and arthritis. Cysteine proteases inhibitors thus have considerable potential utility for therapeutic intervention in a variety of disease states. This review emphasizes on the new developments from literature reports on Michael acceptors as potential cysteine protease inhibitors, namely vinyl sulfones, α,β-unsaturated carbonyl derivatives and aza-peptides. These compounds irreversibly alkylate the active site cysteine residue via conjugate addition. Examples of Michael acceptors inhibitors that have already progressed to clinical testing are also presented.
Keywords: α; β-unsaturated carbonyl derivative